Analysis of Fulfillment of Auditor Requirements in Conducting Audits of Election Participants' Campaign Fund Reports - Arsyad, Muhammad (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2024)
This research aims to find out what requirements must be met by auditors in conducting an audit of campaign finance reports for election participants for the period of 2024-2029 in Indonesia. This research is a literature research, the data analysis method used in this research is descriptive qualitative. The data collection technique was carried out using the library research method, namely study literature that sourced from statutory regulations and literatures relating to what requirements must be met by auditors in auditing the campaign financial reports of election participants. Based on the results of this research, it can be concluded that there are two main requirements that must be met by auditors, both as AP, Chair and Team Member, in conducting an audit of the campaign finance reports of election participants. These requirements are related to Independence and Competence. The independence and competency requirements in this research are different from the results of previous researchs. The requirements for independence from the results of this research are that it is not affiliated directly or indirectly with election participants and/or campaign teams, is not a member or administrator of a political party, or administrator of a political party proposing candidate pairs and does not have the status of a state civil servant. The auditor is required to make a Statement of Independence. The Competency Requirements that must be fulfilled by the Auditor are having attended training and obtained a certificate of competency in auditing Campaign Fund Reports from a valid professional association, must have audit work experience in KAP, and a minimum education of Bachelor's Degree in Accounting for the chairman and 2 (two) years' experience, for Team members have a minimum education of D3 in Accounting and 1 (one) year of experience. The auditor is required to make a statement of work ability.